2014
DOI: 10.1007/s00134-014-3230-y
|View full text |Cite
|
Sign up to set email alerts
|

A randomized trial of intravenous glutamine supplementation in trauma ICU patients

Abstract: There was no benefit with i.v. L-alanyl-L-glutamine dipeptide supplementation (0.5 g/kg body weight/day of the dipeptide) during 5 days in trauma patients admitted to the ICU. The i.v. glutamine supplementation was not enough to normalize the plasma glutamine levels in all patients. Low plasma glutamine levels at day 6 were associated with a worse outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 36 publications
1
17
1
Order By: Relevance
“…We appreciate the comments by Ozcelik et al [1] on our paper on intravenous glutamine supplementation in trauma ICU patients [2]. We agree with Ozcelik on the complex interdependence effects of pharmaconutrients in critically ill patients.…”
Section: Dear Editorsupporting
confidence: 52%
“…We appreciate the comments by Ozcelik et al [1] on our paper on intravenous glutamine supplementation in trauma ICU patients [2]. We agree with Ozcelik on the complex interdependence effects of pharmaconutrients in critically ill patients.…”
Section: Dear Editorsupporting
confidence: 52%
“…A separate group of researchers recently conducted a randomized, multicenter trial to evaluate to effect of 5-day intravenous (IV) glutamine supplementation on trauma ICU patients, finding that 60% of patients had low-plasma glutamine levels, which persisted in 39% of the treated group following randomization to receive 0.5 g/kg/weight IV glutamine. 93 Low-plasma glutamine was also associated with higher rates of infection (59% vs 81%; P = .032), longer ICU (9 vs 20 days; P = .01), and hospital LOS (24 vs 41 days; P = .01) compared with those who received placebo. This is concerning because not only did high-dose supplementation fail to achieve normal plasma glutamine levels, but the dose used was that in which researchers in the previously discussed metaanalysis described a risk factor for increased mortality among critically ill patients.…”
Section: Immunonutrition and Immune-modulating Formulasmentioning
confidence: 89%
“…Recently, Perez-Barsena et al again did not find any beneficial effect of glutamine during 5 days of administration in terms of prevention of new infections. Low levels of glutamine remain unchanged despite administration and were associated as worse outcome [47]. However, Wischmeyer [48], in a meta-analysis including critically ill patients and trauma patients but excluding the recent Heyland study, concluded that IV glutamine should be added in PN in patients without renal and hepatic failure.…”
Section: Macronutrients Vitamins and Trace Elementsmentioning
confidence: 94%